Understand Of Customer Satisfaction And Purchasing Behavior: A Study At Mcdonald In Bandung - Vincentius Leonardo kweeswara; Hadi Kusumah (Syntax Corporation Indonesia, 2020)
This research was created for understand customer purchasing behavior and customer satisfaction in McDonald. This research was focus in Bandung, West Java, Indonesia. Base on history of McDonald, Fast food outlets have started to develop in the 19th century. In the 20th century, fast food restaurant business began to spread to Europe, Africa, Australia and Asia such as Indonesia through franchising or franchise concept. However local business can make competitive market with McDonald. This research will help McDonald to evaluate they performance in market. With this research McDonald can know which area they need to improve and suggestion for McDonald to increase their sales. With this research McDonald can know which are make customer satisfaction and which area make customer dissatisfaction. This research takes six major factors that have impact with customer satisfaction. Those factors are price, quality, promotion, sales personnel or staff, display, and location. This research will use survey method to gain some information from customer. After collect some data and information. This research will use SPSS to process the data to know which hypotheses is accepted and rejected. Method using by this research in SPSS is ANOVA. ANOVA will give a significant point for every question to know the result can accept or reject. Result of this paper base on sic major factor are important. For the crucial factor are The most factor, which have biggest impact, are quality and promotion. Quality and promotion have the lower significant. All value in quality and promotion factor was accepted. It mean quality and promotion are the most influencing factors.